2021
DOI: 10.1007/s00122-021-03800-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and validating stem rust resistance genes directly in self-incompatible genetic resources of winter rye

Abstract: Key message Individual stem rust resistance genes could be directly mapped within self-incompatible rye populations. Abstract Genetic resources of rye (Secale cereale L.) are cross-pollinating populations that can be highly diverse and are naturally segregating. In this study, we show that this segregation could be used for mapping stem rust resistance. Populations of pre-selected donors from the Russian Federation, the USA and Austria were tested on a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Additionally, we identified several large clusters of NLR genes residing in the PM resistance-associated block harboring PmNOS1 in both of the reference genomes. In addition to the PM resistance gene identified in our study, Fusarium head blight and leaf rust resistance genes have been mapped to the subtelomeric region of chromosome arm 7RL 76 , 77 . Stem and stripe rust resistance genes reported in the 7BS:7RL translocation line developed by Ren et al 42 are furthermore likely to reside in the subtelomeric region.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we identified several large clusters of NLR genes residing in the PM resistance-associated block harboring PmNOS1 in both of the reference genomes. In addition to the PM resistance gene identified in our study, Fusarium head blight and leaf rust resistance genes have been mapped to the subtelomeric region of chromosome arm 7RL 76 , 77 . Stem and stripe rust resistance genes reported in the 7BS:7RL translocation line developed by Ren et al 42 are furthermore likely to reside in the subtelomeric region.…”
Section: Discussionmentioning
confidence: 99%
“…Although rye landrace populations have a low degree of genetic differentiation among themselves, distinct open pollinated varieties (OPVs) are maintained by breeding programs. For instance, Gruner et al (2021) sourced five rye populations selected for improved resistance to stem rust from the United States, Austria, and Russia that were either varieties, breeding material or ex situ accessions maintained with known isolation and presented clear differentiation between populations. Rye inbred lines from different breeding programs (university, company) are also differentiated (Targońska-Karasek et al, 2017).…”
Section: Genetic Variation In Breeding Programsmentioning
confidence: 99%
“…Importantly, a pair of recent studies by Gruner et al (2020Gruner et al ( , 2021 conducted genetic mapping in both a testcross mapping population and selfincompatible biparental populations and demonstrated that self-incompatible populations can be used for genetic mapping. Finally, we noted four recent studies that published a validated marker to use in marker-assisted selection (Braun et al, 2019;Gruner et al, 2020Gruner et al, , 2021Rakoczy-Trojanowska et al, 2017). This suggests that there are few publicly available markers due to the quantitative nature of many of these traits.…”
Section: Crop Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to QTL mapping with biparental populations, genome-wide association studies (GWAS) offer a sampling of greater levels of genetic diversity and higher resolution of QTL positions using already existing breeding lines and genetic stocks (Jamann et al, 2015). In rye, GWAS have been reported for the traits leaf rust resistance, preharvest sprouting resistance, and α-amylase activity (Rakoczy-Trojanowska et al, 2017), Tan spot resistance (Sidhu et al, 2019), Fusarium head blight resistance (Gaikpa et al, 2020), and stem rust resistance (Gruner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%